Quality Control with Method Total Quality Management A case study at PT XYZ - ramadhani, hafiz; Susilawati, Anita (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Riau, 2024)
This study aims to evaluate the implementation of Total Quality Management (TQM) at PT XYZ, a pulp manufacturing company, to enhance product quality and operational efficiency. A case study method was used. Data on product defects were collected from PT XYZ and analyzed using three TQM tools: Check Sheets, Histograms, and Pareto Charts. The study also recommends integrating four additional tools for a more comprehensive approach. Among eight defect categories, the most common issue was the Torn Wrapper defect. February's defect rate (0.36%) exceeded the target of 0.30%, indicating room for process improvement. The analysis is limited to descriptive statistics without inferential testing. Future research should apply broader statistical tools and compare findings across multiple companies. This study offers insight into the practical application of TQM in a local pulp industry setting, contributing contextual knowledge to the field.